11w+21(3w-1)=15w

Simple and best practice solution for 11w+21(3w-1)=15w equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11w+21(3w-1)=15w equation:


Simplifying
11w + 21(3w + -1) = 15w

Reorder the terms:
11w + 21(-1 + 3w) = 15w
11w + (-1 * 21 + 3w * 21) = 15w
11w + (-21 + 63w) = 15w

Reorder the terms:
-21 + 11w + 63w = 15w

Combine like terms: 11w + 63w = 74w
-21 + 74w = 15w

Solving
-21 + 74w = 15w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-15w' to each side of the equation.
-21 + 74w + -15w = 15w + -15w

Combine like terms: 74w + -15w = 59w
-21 + 59w = 15w + -15w

Combine like terms: 15w + -15w = 0
-21 + 59w = 0

Add '21' to each side of the equation.
-21 + 21 + 59w = 0 + 21

Combine like terms: -21 + 21 = 0
0 + 59w = 0 + 21
59w = 0 + 21

Combine like terms: 0 + 21 = 21
59w = 21

Divide each side by '59'.
w = 0.3559322034

Simplifying
w = 0.3559322034

See similar equations:

| 2-1/7x=4 | | 3+12x-5=22 | | 25(4x+2)=150 | | 8x+3y-5x+7-10y+2= | | 4x-12x-12x+36=4x^2+36 | | (7j-h)(7j-h)(7j-h)= | | x^2+105=5 | | ln(2)=.69 | | 3n+5n=8 | | 1-x-6x=-6 | | X+6-3=-3 | | 13(9x-6)=6x-4 | | w+1.2=16.2 | | 12.12=3v | | (4x-5y+3z)+(-4x+5y+3z)= | | 2(3R-2)=4(R+4) | | -139-2x=57-9x | | 15+4x=7x+48 | | 12-(x-12)=4 | | 3(1-3x)=-8g+14 | | -2(5+5x)=-120 | | 20=3x-x+6 | | -3(7x+4)=-12 | | -7=5x+7x-7 | | 12-3(2x+1)=4w-21 | | 35(5)+.08x=25(5)+.25x | | 33xy/3x | | -2x+2-6x=34 | | 3(45)+6x=303 | | 2x+2-6x=34 | | 5n-10=8n-14 | | 12x-3=20x-9 |

Equations solver categories